Policy Formulation Of Violence In The Teaching Learning Process Reviewed From The Perspective Of Criminal Law - Felisitas Novela Andrea Ardhinata (Veteran Justice Journal, 2021)
Abstract Legal norms in the formulation of violence in the teaching and learning process from a criminal law perspective are contained in Law Number 35 of 2014 concerning Amendments to Law Number 23 of 2002 concerning Child Protection. The stipulation of Perpu Number 1 of 2016 concerning the Second Amendment to Law Number 23 of 2002. The formulation of the problems in this study are: 1) How is the policy of formulating criminal acts of violence in the teaching and learning process in the perspective of Indonesian criminal law? 2) How is the implementation of the formulation of violent crime policies in the teaching and learning process from the perspective of Indonesian criminal law? The author uses an empirical juridical approach, which is an approach that is carried out by studying the law in fact in the form of attitudes, judgments, behaviors, which are related to the problems being studied and which are carried out by conducting research in the field. Based on the research results, it can be concluded that: 1) The government welcomes this by issuing Law Number 17 of 2016 concerning Stipulation of Government Regulations in Lieu of Law Number 1 of 2016 concerning the Second Amendment to Law Number 23 of 2002 concerning Child Protection. Constitution. 2) The implementation of the formulation of violence in teaching and learning is still not optimal. One of the problems is that if schools and teachers are less assertive, students are free so they don't heed existing norms and regulations. For example, students will appear arbitrarily like thugs, free to skip school without harsh penalties, be free to commit delinquency beyond normal limits, underestimate teachers, and so on. Keywords: Policy, Violence, Teaching and Learning